Obrazy – nie tylko w wyobraźni. Wizualna ewolucja radia - Wójciszyn-Wasil, Aneta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
For years, the immanent feature of the radio was avisuality. Pictures functioned only in the context of reflections on perceptual impressions produced in the listener’s imagination. Thanks to the expansion of the Internet, images in the radio have become reality. While retaining the analogue signal, the modern radio is also a producer of multimedia contents published in many distribution platforms. It uses photographs and video, co-operates with the TV and is visible in social media. The article deals with selected aspects of the visual evolution of the radio: the provision of picture from the studio, the project of a radio with vision, common programmes of radio and TV stations. It also shows how photographs and video footages are used for building a relation with the recipient.